Data acquisition in multiple-sink sensor networks. - Das, Abhimanyu
Scalable, energy-efficient data acquisition in large sensor network deployments such as habitat monitoring is an research important problem. In several papers [1, 2], sensor networks have been modeled as having a single sink (or base-station) that acts as the data recipient for a large number of sensors (data sources) deployed over a sensor field. The sensor network might use simple querying and data collection trees for hop-by-hop query dissemination and routing of sensor responses [1] back towards the sink. Since sensors are energy-constrained devices, we wish to minimize communication energy expenditure of these sensors.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Data communications; Design; Experimentation; Measurement; Performance; General